Editorial - Compton, R (2007)
The development of Electrochemistry Communications, a scientific journal, due to strategic business planning and standards followed by the journal for selection of research papers, are presented. Electrochemistry Communications started publishing of research papers related to the field of electrochemistry in January 1999, with the publication of 12 articles. The journal received over thousand papers in 2006, which prompted decline in acceptance rate to ca. 40% of scientific papers. The journal has attained status of the specialist electrochemistry journal due to its high Impact Factor. The huge increase in the submission rates led to development of stringent standards for acceptance of scientific papers. The paper of Professor Joe Wang and his colleagues on the voltammetry of carbon nanotube modified electrodes provided vital information regarding electroanalytical chemistry.